Isolation and screening of multifunctional rhizobacteria from the selected sites of Madhupur, Narshingdi and Mymensingh, Bangladesh (Research in Agriculture Livestock and Fisheries, 2015)
A laboratory experiment was performed to isolate some native rhizobacteria that could be used as bioinoculants for sustainable crop production. A total of 43 rhizobacteria were isolated from undisturbed plant rhizosphere soils of three different locations of Bangladesh and evaluated their plant growth promoting traits, both direct and indirect. The study has screened out isolates on the basis of their phosphorous solubilization and nitrogen (N) fixation. The phosphate solubilization assay in National Botanical Research Institute of Phosphate (NBRIP) medium revealed that 12 bacterial isolates were able to solubilize tricalcium phosphate and the rhizobacteria M25 showed best performance with a PSI of 3.33 at 5 day. Exactly 47% (20 isolates) of the isolated rhizobacteria were able to grow in N-free Winogradskys medium, which is an indication of potential N2-fixers. Among the 20 potential N-fixers, 15 were able to grow within 24 hours of incubation indicating that they are more efficient in Nfixation. The present study successfully isolated and characterized 43 rhizobacteria. Some of these isolated rhizobacteria have potential plant growth promoting traits and are potential plant growth promoting rhizobacteria (PGPR) candidate. Considering all plant growth promoting traits, the isolate F37 was the best followed by M6. However, further experiments are needed to determine the effectiveness of these isolates under in vitro and different field conditions to understand the nature of interaction with the plant and environment.Res. Agric., Livest. Fish.2(1): 1-8, April 2015